Tribologically enhanced self-healing hybrid laminates for wind turbine applications - Hasırcı, Kemal; Ergene, Berkay; Irez, Alaeddin Burak (Wiley, 2024)
Wind turbines are subjected to extreme weather and load conditions; hence, high strength and impact resistance are required. Furthermore, wind turbine blades can be subjected to impact loads such as bird strikes, resulting in the formation of microcracks. Self-healing capsules can be used to mend turbine blades for microscale damage. The incorporation of self-healing capsules may cause a decrease in the mechanical characteristics of the composites prior to impact resistance, which can be compensated for with efficient fillers such as silicon carbide whiskers (SiCw). Thus, a novel hybrid composite structure is examined with the advantage of using a self-healing mechanism and SiCw reinforcement. Tensile, tribological, and Charpy impact tests were performed to characterize the mechanical and tribological properties, which were supported with microscopic observations. Multiple experimental characterizations were performed to investigate the impact, and the ultimate tensile strength (UTS) and energy absorption capacity of the structure were shown to increase by 32% and 45%, respectively, with the addition of SiCw. The presence of self-healing agents provides a 5% rise in UTS after enough time for healing following the collision. The structure's tribological performance is improved by 10% in wear resistance and 20% in friction coefficient. Highlights Hybrid laminated composite structure with silicon carbide whisker and self-healing capsules. Tensile and Charpy impact tests conducted with microscopic observations Increased ultimate tensile strength and energy absorption capacity by 32% and 45%. Tribological improvement by 10% in wear resistance and 20% in friction coefficient.
Keywords: bird strikes; composites; self-healing; carbide whiskers; wind turbines; wind power